Elevated cerebrospinal fluid uric acid during relapse of neuromyelitis optica spectrum disorders. Issue 1 (21st October 2016) - Shu, Yaqing; Li, Haiyan; Zhang, Lei; Wang, Yuge; Long, Youming; Li, Rui; Qiu, Wei; Lu, Zhengqi; Hu, Xueqiang; Peng, Fuhua
Abstract: Introduction: Previous studies have shown that serum uric acid (UA) modulates outcomes of neurological diseases, although little is known about cerebrospinal fluid (CSF) UA levels in neuromyelitis optica spectrum disorders (NMOSDs). Methods: Cerebrospinal fluid and serum UA levels were measured in samples from 68 patients, including NMOSDs during relapse ( n = 38) and controls with noninflammatory and non‐neurodegenerative diseases (CTLs, n = 30). Correlation analysis was performed between CSF UA and clinical characteristics, serum UA, and blood–brain barrier integrity in NMOSDs. Results: Cerebrospinal fluid UA levels in NMOSDs were significantly higher than in CTLs ( p = .002), while serum UA differences between NMOSDs and CTLs were not statistically significant. In NMOSDs, CSF UA levels were significantly higher in patients with an impaired blood–brain barrier than in patients with an intact one ( p < .001), and significantly higher in longer disease duration than in shorter disease duration patients ( p = .002). CSF UA levels were also significantly higher in active patients upon MRI than in inactive patients ( p < .001), and significantly higher in patients with brain lesions than without brain lesions ( p = .024). CSF UA was significantly associated with the serum UA levels ( r = .454, p = .002), disease duration ( r = .383, p = .018), and blood–brain barrier index ( r = .805, p < .001), but did not correlate with age, gender, annualized relapse rate, duration, or severity of NMOSD. Multiple regression analysis demonstrated that CSF UA was independent of the blood–brain barrier index (β = .765, p < .001) and serum UA levels (β = .01, p = .019) in NMOSDs. Conclusions: Cerebrospinal fluid UA levels were elevated in NMOSD patients during relapse, and were likely modified by serum UA levels and blood–brain barrier integrity. Abstract : Cerebrospinal fluid UA levels were elevated in patients with NMOSDs during relapse, and were likely modified by serum UA and blood–brain barrier integrity.